2021
DOI: 10.1080/14790718.2021.1960534
|View full text |Cite
|
Sign up to set email alerts
|

Does the Complementarity Principle apply to inner speech? A mixed-methods study on multilingual Chinese university students in the UK

Abstract: This paper investigates how inner speech in English as a foreign language (LX) and Chinese first languages (L1s) of 425 multilingual Chinese university students in the UK is affected by their stay. An eight-item scale was developed to cover two different discourse domains for inner speech, namely the academic and the general domain. LX socialization was operationalized as frequency of English use in daily life, sociocultural adaptation, previous immersion, and length of stay. Factor analysis of the quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…P2 s Scottish Gaelic was acquired in a classroom context but heard coming from a voice reminiscent of a family member; P5 s home and family languages were spoken by voices associated with a workplace context. This differs from inner speech patterns: for example, students speaking English as an LX adopt academic inner speech more than general inner speech, reflecting the domain and context of acquisition (Leung & Dewaele, 2021).…”
Section: Reflection and Refractionmentioning
confidence: 92%
See 1 more Smart Citation
“…P2 s Scottish Gaelic was acquired in a classroom context but heard coming from a voice reminiscent of a family member; P5 s home and family languages were spoken by voices associated with a workplace context. This differs from inner speech patterns: for example, students speaking English as an LX adopt academic inner speech more than general inner speech, reflecting the domain and context of acquisition (Leung & Dewaele, 2021).…”
Section: Reflection and Refractionmentioning
confidence: 92%
“…Inner speech language use can be affected by: acquisition and use context, and network size (Dewaele, 2015;Guerrero, 2018); degree of L1-LX difference (Resnik, 2021); topic or function (Hammer, 2017;; and emotionality, with emotional LX inner speech taking longer to develop (Dewaele, 2015;Guerrero, 2018). Leung and Dewaele (2021) found that (2012) Complementarity Principle, according to which language preferences differ according to situations, interlocutors, and purposes, applies also to inner speech. Some studies, like Hadden et al (2020) controlled the language profiles of participants.…”
Section: Howevermentioning
confidence: 99%